2020
DOI: 10.1101/2020.04.03.20047977
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ACE2gene variants may underlie interindividual variability and susceptibility to COVID-19 in the Italian population

Abstract: In December 2019, an initial cluster of unexpected interstitial bilateral pneumonia emerged in Wuhan, Hubei province. A human-to-human transmission was immediately assumed and a previously unrecognized entity, termed coronavirus disease 19 (COVID-19) due to a novel coronavirus (2019-nCov) was suddenly described. The infection has rapidly spread out all over the world and Italy has been the first European Country experiencing the endemic wave with unexpected clinical severity in comparison with Asian countries.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…Structural analysis of variation in human ACE2 . We applied the same approach used to compare species, sequence identity and protein structural analysis, to examine the variation in ACE binding residues within humans, some of which have been proposed to alter binding affinity (18,(27)(28)(29)(30) . We integrated data from six different sources: dbSNP (31) , 1KGP (32) , Topmed (33) , UK10K (34) and CHINAMAP (28) , and identified a total of 11 variants in ten of the 25 ACE2 binding residues (Dataset S2).…”
Section: Resultsmentioning
confidence: 99%
“…Structural analysis of variation in human ACE2 . We applied the same approach used to compare species, sequence identity and protein structural analysis, to examine the variation in ACE binding residues within humans, some of which have been proposed to alter binding affinity (18,(27)(28)(29)(30) . We integrated data from six different sources: dbSNP (31) , 1KGP (32) , Topmed (33) , UK10K (34) and CHINAMAP (28) , and identified a total of 11 variants in ten of the 25 ACE2 binding residues (Dataset S2).…”
Section: Resultsmentioning
confidence: 99%
“…Genetics may also play a role through polymorphisms of genes which encode for 1) proteins that are exploited by SARS-CoV-2, such as the highly conserved Angiotensin Converting Enzyme 2 (ACE2), which, as was also the case for SARS-CoV, it uses for docking and cellular entry in respiratory cells, or 2) proteins which provide protection against the effects of the virus (such as surfactant proteins, but also ACE2 itself) 22 . Genetic association studies are currently ongoing to unravel such hypotheses, and have found correlations between ACE2 variants and COVID-19 susceptibility 23,24 . Interestingly, as an X-linked phenotype, the effectiveness of interaction-booster and interaction-inhibitor variants of ACE2 can be more definite in males than females, and could contribute towards a higher mortality rate in males, accounting for up to ∼70% of death caused by SARS-CoV2, SARS-CoV or MERS-CoV 25 , in addition to a likely higher rate of risk factors (e.g.…”
Section: Genetics In Covid-19mentioning
confidence: 99%
“…No reuse allowed without permission. SARS-CoV-2 virus is a single stranded (+) sense RNA virus with a genome length of about 30 Kb. It encodes 29 structural and non-structural proteins, including ORF1a/b polyprotein, spike (S) glycoprotein, envelope (E), membrane (M) and the nucleocapsid (N) protein (8,17).…”
Section: Introductionmentioning
confidence: 99%
“…In ACE2, the majority of observed variants occur at low frequencies (non-polymorphic) in most human populations. Even though some recent studies (29,30) have attempted to implicate these variants with susceptibility to infection by SARS-CoV-2, there is no convincing evidence yet that the lowfrequency, non-polymorphic variants in ACE2 can modulate susceptibility to SARS-Cov-2 infection.…”
Section: Introductionmentioning
confidence: 99%